2012
DOI: 10.1002/jcu.21997
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings in three cases of carcinoma showing thymus‐like differentiation

Abstract: Carcinoma showing thymus-like differentiation (CASTLE) is a rare tumor of the thyroid gland or soft tissues of the head and neck. To our knowledge, there have been only a few reports concerning imaging findings of CASTLE. We report herein the sonographic appearances of three cases of CASTLE. Two tumors were located at the lower part of the thyroid and one had spread throughout the thyroid. Sonograms showed heterogeneously solid tumors without cystic components or calcification. The central part of the tumor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
3
11
0
1
Order By: Relevance
“…In the present study, ultrasound imaging of CASTLE identified a solid and hypoechoic mass, whose echo was typically heterogeneous. Yamamoto et al ( 15 ) studied the sonographic findings in three cases of CASTLE and concluded that CASTLE was solid and hypoechoic, with a heterogeneous echo pattern and without cystic components or calcifications, which is in agreement with the results of the present study. CASTLE was previously described as ‘cold nodule’ in ECT, suggesting that it was a malignancy ( 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, ultrasound imaging of CASTLE identified a solid and hypoechoic mass, whose echo was typically heterogeneous. Yamamoto et al ( 15 ) studied the sonographic findings in three cases of CASTLE and concluded that CASTLE was solid and hypoechoic, with a heterogeneous echo pattern and without cystic components or calcifications, which is in agreement with the results of the present study. CASTLE was previously described as ‘cold nodule’ in ECT, suggesting that it was a malignancy ( 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Pre-operative diagnosis of CASTLE is generally difficult, not only due to its non-specific clinical features, but also due to the lack of characteristic radiological features. Ultrasound features reported by Yamamoto et al include heterogeneously solid tumors without cystic components or calcification, and the central part of the tumor was reported to be slightly hyperechoic compared with the peripheral part of the tumor [8]. On non-contrast CT scans, the tumors are ill-defined and nodular, with uniform density.…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasound, CASTLE can be lobulated, solid, hypoechoic tumours without cystic components or calcification with heterogeneous internal echoes. 8 On plain CT scan, uniform isodensity could be seen in most tumours without calcification; cystic change is also rare, only in one case. On contrast-enhanced CT, mild enhancement was generally noted.…”
Section: Pathological Findingsmentioning
confidence: 82%
“…Until now, ,100 cases have been reported in the English literature, and the radiological imaging findings are solely limited to individual case reports. [6][7][8] Given the rarity of CASTLE, most radiologists are not familiar with it. Thus, we intend to report the CT and MR imaging appearances of 10 cases of CASTLE in this study along with a review of the relevant literature and also wish to raise awareness of this uncommon thyroid malignancy.…”
Section: Introductionmentioning
confidence: 99%